The Importance of Stem Cells as Praxis in the Development of Current Regenerative Medicine: Soraya Rahmanisa, Evi Kurniawaty, Rika Lisiswanti - Soraya Rahmanisa; Evi Kurniawaty; Rika Lisiswanti (Jurnal Kedokteran Universitas Lampung, 2026)
ABSTRACT For almost a century, the foundation of modern medicine has been the same: determine the underlying cause of the illness, then prevent or treat it. Antibiotics kill bacteria. Beta-blockers inhibit adrenergic receptors. Insulin replaces the hormone that is not produced. This approach is extraordinarily effective — but it has a fundamental limitation: it does not restore the damaged biological capacity, it manages it. Stem cells offer something categorically different: the ability to regenerate damaged tissues and organs from the most fundamental level — the cellular level. This is not a difference of degree, but a difference of kind. Stem cells occupy a central position in the revolution of regenerative medicine — a paradigm aimed at restoring the function of damaged tissues and organs, rather than merely managing symptoms. This review presents recent evidence (2019–2026) on the role of stem cells as praxis — scientific actions informed by values and oriented toward the restoration of human capabilities. This article examines the applications of stem cells in the fields of neurology, cardiology, oncology, endocrinology, and tissue engineering, as well as mapping the translational challenges and their implications for global health policy.